Revolutionizing Urban Growth: Exploring Novel Theories and Models for Integrated Development of Industries and Cities (IDIC) - Libin Guo (Revolutionizing Urban Growth: Exploring Novel Theories and Models for Integrated Development of Industries and Cities (IDIC), 2023)
This book first provides an explanation of the connotation and concept of the development of industry-city integration. It then analyzes case studies of industry-city integration development in typical foreign cities outside of China. Following that, it compares China with other countries, analyzing the overall situation of industry-city integration development in China and comparing it with other countries. Finally, the book conducts specific analysis of case studies of industry-city integration development within China, and provides development needs and recommendations.